Farmaci orfani e malattie rare: la situazione in Italia - Martina, S.; Denti, C.; Daina, E.; Garattini, L. (Farmeconomia. Health Economics and Therapeutic Pathways, 2001)
Aim of this study is to check the Italian market of the orphan drugs in connection with rare diseases. Data for the research have been found on the Food and Drug Administration Database, the Centro di Ricerche Cliniche per le Malattie Rare “Aldo e Cele Daccò” Database and L’informatore farmaceutico. This study also compared the Italian market with the American market, that counts the greater number of designated orphan drugs and commercial authorizations in the world. In Italy only 24 orphan drugs have been authorized by the Ministry of Health and the present work analyzes their definition under the economic profile, how many diseases and what kind of pathologies they can treat, the number of products on the market and if they are refundable or not.